Strengthening child protection : sharing information in multi-agency settings - Thompson, Kellie (Policy Press, 2016)
Following high-profile Serious Case Reviews into the tragic deaths of children, including Victoria Climbie, Peter Connelly, and Daniel Pelka, information sharing has now become a moral and political imperative for safeguarding the welfare of children. What prompts information sharing and how do we get it right? This accessible book challenges widely held assumptions about information sharing in child welfare that facts about risks to children are clear and that sharing them with other professionals is a straightforward process. End-of-chapter questions prompt reflection and ensure direct practice relevance. This is essential reading for academics and policy makers, students on post-qualifying child protection courses, social workers, managers and all other professionals tasked with safeguarding children.